A remark on the stability of peakons for the Degasperis–Procesi Equation. (February 2016) - Kabakouala, André
Abstract: In this paper, we present a new argument (seeLemma 3.4 ) that allows us to simplify the proof of stability of peakons established in Lin and Liu (2009) (Theorem 1.1).